30. EVALUATION OF RESULTS AFTER TRANSURETHRAL ENDOSCOPIC SURGERY FOR ADVANCED PROSTATE CANCER WITH BIDUAL ORCHECTOMY AT VIET DUC HOSPITAL FROM 1/2018 - 12/2022 (Vietnam Journal of Community Medicine, 2025)
Abstract: The study aimed to evaluate the results after transurethral endoscopic resection of advanced prostate cancer with bilateral orchiectomy at Viet Duc Hospital from January 2018 to December 2022.Subjects and methods: The retrospective method followed up longitudinally on 217 patients diagnosed with advanced prostate cancer who underwent transurethral resection of the tumor with bilateral orchiectomy.Results: Most of the patients were in stages T3, T4 accounting for 82.9%, early stage T2 accounting for only 17.1%. Of the 217 patients, 118 were alive (54.4%), 99 patients (45.6%) died. The survival rate decreased gradually over the follow-up time of the groups from 24 to 72 months after surgery, corresponding to 67.1% to 36.8%. The main cause of death was cancer metastasis to other organs. Factors affecting survival rate and overall survival time were Gleason score, age group and stage of  Prostate cancer  (p
Keywords: prostate cancer; postoperative outcome assessment; survival rate